Pengaruh Nutrisi dan CaCl2 terhadap Pertumbuhan dan Hasil Tanaman Selada (Lactuca sativa L.) secara Hidroponik Sistem Wick - Safitri, Nurul; Millah, Zahratul; Romdhonah, Yayu; Sodiq, Abdul Hasyim (Jurnal Agroekoteknologi, 2024)
This study aimed to determine the effect of providing a combination of hydroponic nutrition and the addition of CaCl2 on the growth and yield of hydroponic lettuce (Lactuca sativa L.) with a wick system. The research was conducted at the Agricultural Instrument Standardization Center Banten Province and Lingkungan Sapiah, Panancangan, Cipocok Jaya, Serang City from April to June 2023. This study used a factorial Randomized Block Design (RBD) consisting of two factors. The first factor was a combination of nutrients with 3 levels, namely A1 (AB Mix 3 ml/l), A2 (AB Mix 1.5 ml/l + POC Nasa 3 ml/l), A3 (AB Mix 1.5 ml/l + Gandasil D 3 ml/l). The second factor was the concentration of CaCl2 with 2 levels, namely C1 (0 ppm) and C2 (650 ppm). The parameters observed were plant height, number of leaves, root length, stem diameter, plant wet weight, crown weight, weight loss, and stem hardness of lettuce. The results showed that the combination of AB Mix 3 ml/l + POC Nasa 3 ml/l gave he best effect on plant height 35 days after planting (DAP) (23.54 cm), number of leaves 35 DAP (7.81 leaves). The addition of CaCl2 concentrationof 650 ppm gave the best effect weight loss on 3 DAH (54.48%), 4 DAH (66.51%), 7 DAH (85.99%), and stem hardness on 0 DAH (0.96), 2 DAH (0.80), and 4 DAH (0.64). There was an interaction between the hydroponic nutrient combination treatment and the addition of CaCl2 on the parameters of plant height and number of leaves on 35 DAP.